Physiological and molecular implications of multiple abiotic stresses on yield and quality of rice - Radha, Beena; Sunitha, Nagenahalli Chandrappa; Sah, Rameswar P.; T. P., Md Azharudheen; Krishna, G. K.; Umesh, Deepika Kumar; Thomas, Sini; Anilkumar, Chandrappa; Upadhyay, Sameer; Kumar, Awadhesh; Ch L. N., Manikanta; S., Behera; et al. (Frontiers in Plant Science, 2023)
Abiotic stresses adversely affect rice yield and productivity, especially under the changing climatic scenario. Exposure to multiple abiotic stresses acting together aggravates these effects. The projected increase in global temperatures, rainfall variability, and salinity will increase the frequency and intensity of multiple abiotic stresses. These abiotic stresses affect paddy physiology and deteriorate grain quality, especially milling quality and cooking characteristics. Understanding the molecular and physiological mechanisms behind grain quality reduction under multiple abiotic stresses is needed to breed cultivars that can tolerate multiple abiotic stresses. This review summarizes the combined effect of various stresses on rice physiology, focusing on grain quality parameters and yield traits, and discusses strategies for improving grain quality parameters using high-throughput phenotyping with omics approaches.